Waktu Dan Jarak Efektif Penyinaran Sinar Ultraviolet Pada Mikroba Udara Laboratorium - Elisa Rinihapsari; Arneta Syafrinelty Fita Putri; Bernadeta Hesti Widyaningrati (Universitas Muhamadiyah Manado, 2021)
Ultraviolet light is commonly used as a laboratory sterilization method to complement chemical sterilization. Until now, there has been no standard reference for the use of exposure time and exposure distance that can be effectively used for sterilizing laboratory rooms. Based on this, it is necessary to conduct this research to test the effectiveness of ultraviolet irradiation in the laboratory with varying exposure times, including 0.5, 1, 1.5, and 2 hours with an irradiation distance of 1, 1.5, and 2 meters. This experimental research was conducted at the Medical Laboratory of the Mangunwijaya Catholic Polytechnic of Medical Laboratory Technology Program. Capture of airborne microbes using the settle plate method. The results showed that the percentage reduction in the number of microbes before and after irradiation was 96.30, 62.97, 85.18, and 59.26 CFU/m3, respectively, for exposure time 0.5, 1, 1.5, and 2 hours, while the percentage decrease in the number of microbes for distance 1; 1.5; and 2m is 66.67; 67.74; 64.71 CFU/m3. The conclusion was that the adequate time to reduce the number of air microbes was 0.5 hours, while the effective distance was 1.5m.